Birzeit Municipality: Its Origin and Development during Jordanian Rule 1963-1967AD : Municipal Council Records as a Source - ALQudah, Ahmad Hamed Ibraheem (Jordan Journal for History and Archaeology, 2025)
The main aim of this research is to present a comprehensive study of the municipality of Birzeit, which was established in 1963 AD, based on its records during the study period. The research delved the establishment of the municipality, its borders, its headquarters, the meetings of the municipal council, its employees, the structural organization of the city of Birzeit in 1962 AD and 1965 AD, the impacts on the development of the city and the residents’ attitudes towards it. The research also discussed the role of the municipality in providing basic services to citizens, such as opening the streets and supplying electricity and water to the city, maintaining its cleanliness, and supporting education system in the city. Additionally, the research presented the economic situation, by talking about its annual budget and its revenues from fees and taxes. The research concluded that the laws and regulations issued by the Jordanian government, such as the Municipalities Law in 1955 AD and the structural organization of the city of Birzeit during the years 1962 AD and 1965 AD, contributed to organizing and advancing the work of the Birzeit Municipality. The city witnessed an architectural renaissance, accompanied by supplying the basic services to citizens, such as water and electricity. Members of Christian families in Birzeit also administered the presidency of the city’s municipal council during the study period. The municipal council’s records are an important source that documented the developments that the city of Birzeit witnessed through the decisions taken by the municipal council.